The Impact of Activin A on Fetal Gonocytes: Chronic Versus Acute Exposure Outcomes - Moody, Sarah C.; Whiley, Penny A. F.; Western, Patrick S.; Loveland, Kate L. (Frontiers in Endocrinology, 2022)
Activin A, a TGFβ superfamily member, is important for normal testis development through its actions on Sertoli cell development. Our analyses of altered activin A mouse models indicated gonocyte abnormalities, implicating activin A as a key determinant of early germline formation. Whether it acts directly or indirectly on germ cells is not understood. In humans, the fetal testis may be exposed to abnormally elevated activin A levels during preeclampsia, maternal infections, or following ingestion of certain medications. We hypothesized that this may impact fetal testis development and ultimately affect adult fertility. Germ cells from two mouse models of altered activin bioactivity were analysed. RNA-Seq of gonocytes purified from E13.5 and E15.5 Inhba KO mice (activin A subunit knockout) identified 46 and 44 differentially expressed genes (DEGs) respectively, and 45 in the E13.5 Inha KO (inhibin alpha subunit knockout; increased activin A) gonocytes. To discern direct effects of altered activin bioactivity on germline transcripts, isolated E13.5 gonocytes were cultured for 24h with activin A or with the activin/Nodal/TGFβ inhibitor, SB431542. Gonocytes responded directly to altered signalling, with activin A promoting a more differentiated transcript profile (increased differentiation markers Dnmt3l, Nanos2 and Piwil4; decreased early germ cell markers Kit and Tdgf1), while SB431542 had a reciprocal effect (decreased Nanos2 and Piwil4; increased Kit). To delineate direct and indirect effects of activin A exposure on gonocytes, whole testes were cultured 48h with activin A or SB431542 and collected for histological and transcript analyses, or EdU added at the end of culture to measure germ and Sertoli cell proliferation using flow cytometry. Activin increased, and SB431542 decreased, Sertoli cell proliferation. SB431542-exposure resulted in germ cells escaping mitotic arrest. Analysis of FACS-isolated gonocytes following whole testis culture showed SB431542 increased the early germ cell marker Kit, however there was a general reduction in the impact of altered activin A bioavailability in the normal somatic cell environment. This multifaceted approach identifies a capacity for activin A to directly influence fetal germ cell development, highlighting the potential for altered activin A levels in utero to increase the risk of testicular pathologies that arise from impaired germline maturation.